PHYSICAL CULTURE IN EXTRACURRICULAR ACTIVITIES AS FORMING A HEALTHY LIFESTYLE FOR YOUNG PEOPLE (Pedagogy of Higher and Secondary Education, 2002)
In the article author analyses the different forms of physical culture in the past and the present. The author notes that physicalculture of nowadays must formulate the style of the modern student, learn him to support the necessary state of health.